Analisa Penggunaan Deiksis dalam Lirik Lagu Album Am Karya Arctic Monkeys - Lilis Indah Rohmawati (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2025)
This study analyzed the use of deixis in the lyrics of Arctic Monkeys' AM album to understand its contribution to narrative meaning and emotional connection with listeners. The purpose of the study was to explore how linguistic elements, particularly deixis, function as pragmatic tools in popular music. Using Levinson's (1983) theory, the study identified five types of deixis: persona, spatial, temporal, social, and discourse. The analysis examined their functions in the pragmatic context of song lyrics. According to the rules, the results showed a dominant pattern of person deixis, which strengthened the emotional connection between the narrator and the listener. Additionally, temporal and spatial deixis enriched the narrative by emphasizing time and place contexts. These findings suggested that linguistic elements in song lyrics reinforced emotional and narrative experiences. This study concluded that deixis contributed significantly to enhancing listeners' emotional and narrative engagement, offering valuable insights into the use of language in creative media such as music and the broader study of pragmatics.